Wordwall: Media for Enriching Vocabulary of Sixth Graders - Damayanti, Putu Julia Nirmala; Utami, I G A Lokita Purnamika; Suprianti, G. A. P (Linguistic, English Education and Art (LEEA) Journal, 2024)
This study explores the development and implementation of Wordwall-based educational games designed to supplement the "My Next Word" book for sixth-grade students in SD Negeri 1 Baktiseraga Singaraja, Indonesia. The research aimed to enhance vocabulary acquisition through interactive and engaging digital learning experiences aligned with the Merdeka Curriculum's educational objectives. Various game types were developed, integrating multimedia elements such as images and audio to enrich the learning process. The study followed a structured approach, including blueprint formulation, iterative development, quality assessment, and real-world testing to optimize educational effectiveness. Findings highlight the potential of digital educational games in supporting language learning and fostering student engagement in primary school environments. Keywords: Digital Learning, Primary Education, Vocabulary Acquisition, Wordwall Educational Games